Design and Implementation of Smart Non-Invasive Bone Conduction Ear-Plug System - Ravichandran G; M Krishnamurthy (Institute of Advanced Engineering and Science, 2018)
The project aim is to design a smart earplug system integrated with non-invasive bone conduction technique which is capable of doing some advanced audio processing to provide voice enhancing, noise filtered audio for the hearing impaired people [2]. The system is also designed to work as an embedded music player, a life activity tracker and a Smartphone companion. It can even read the SMS that is just received on your smartphone into your ear. This project needs a very low power microcontroller but with high-performance signal processing requirements. STM32L476 from STMicroelectronics meets this needs and thus chosen as the main MCU. It is an ultra-low power ARM Cortex-M4 based microcontroller that can run up to 80MHz. It has got 1MB of Flash memory and 128 KB RAM.